Icariin Ameliorates Lower Back Pain in Rats via Suppressing the Secretion of Cytokine-Induced Neutrophil Chemoatractant-1. (5th August 2020) - Li, Jitian; Luo, Manli; Wang, Shaochun; Jin, Guoguo; Han, Zongchang; Ma, Yan; Tang, Guoqing; Guo, Zhiping
Abstract : Purpose . To investigate whether icariin (ICA), a well-known medicine extracted from the stem and leaf of Epimedium brevicornum Maxim, had analgesic effect on lower back pain (LBP) in rats. Methods . In a puncture-induced LBP rat model, the severity of LBP was quantified using the paw/foot withdrawal threshold method after intragastric administration of ICA at a dosage of 50 mg/kg/d or 100 mg/kg/d. The pain-related peptides of substance P (SP) and calcitonin gene-related peptide (CGRP) were also measured in intervertebral disc (IVD) tissue using RT-PCR after ICA treatment. In addition, the expression of cytokine-induced neutrophil chemoattractant-1 (CINC-1) in IVD was quantified using RT-PCR and ELISA examination. Results . ICA treatment resulted in a significant amelioration of mechanical allodynia in a dose-response manner, and the analgesic effect could last for two weeks even during the washout period. More importantly, the mechanism of analgesic pharmacological effect in ICA was to suppress the upregulated CINC-1, the homolog of IL-8 in rats, which is a crucial proalgesic factor contributing to LBP, in IVDs. Conclusion . ICA is a novel herbal extract to relieve LBP, and it may be a promising alternative pain killer in the future.